Mass Transfer in Hierarchical Silica Monoliths Loaded With Pt in the Continuous-Flow Liquid-Phase Hydrogenation of p-Nitrophenol - Jatoi, Haseeb Ullah Khan; Goepel, Michael; Poppitz, David; Kohns, Richard; Enke, Dirk; Hartmann, Martin; Gläser, Roger (Frontiers in Chemical Engineering, 2021)
Sol-gel-based silica monoliths with hierarchical mesopores/macropores are promising catalyst support and flow reactors. Here, we report the successful preparation of cylindrically shaped Pt-loaded silica monoliths (length: 2 cm, diameter: 0.5 cm) with a variable mean macropore width of 1, 6, 10, or 27 μm at a fixed mean mesopore width of 17 nm. The Pt-loaded monolithic catalysts were housed in a robust cladding made of borosilicate glass for use as a flow reactor. The monolithic reactors exhibit a permeability as high as 2 μm2 with a pressure drop below 9 bars over a flow rate range of 2–20 cm3 min−1 (solvent: water). The aqueous-phase hydrogenation of p-nitrophenol to p-aminophenol with NaBH4 as a reducing agent was used as a test reaction to study the influence of mass transfer on catalytic activity in continuous flow. No influence of flow rate on conversion at a fixed contact time of 2.6 s was observed for monolithic catalysts with mean macropore widths of 1, 10, or 27 µm. As opposed to earlier studies conducted at much lower flow velocities, this strongly indicates the absence of external mass-transfer limitations or stagnant layer formation in the macropores of the monolithic catalysts.